2015
DOI: 10.1074/jbc.m115.638080
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Laboratory Evolution of Ordered and Disordered Enzymes

Abstract: Background: Intrinsic protein disorder has been hypothesized to be advantageous for protein evolution. Results: Parallel evolution of structured and disordered dihydrofolate reductases afforded comparable increases in activity without substantially changing the dynamic properties of the starting scaffolds. Conclusion: Ordered and disordered enzymes can be similarly evolvable. Significance: Understanding how structural (dis)order influences evolutionary pathways may aid efforts to engineer existing proteins for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…In the case of C45, despite the dynamic nature of the protein, certain characteristics imply that it is a stable, water impenetrable structure [ 22 •• ]. Similar structural characteristics have been observed in other de novo [ 36 ] and natural proteins [ 57 ]. In many of these cases this may be due to the substrate conferring structural homogeneity on the active site, it remains to be experimentally determined whether this is the case for C45.…”
Section: How Important Is a Defined Structure In Catalysis?supporting
confidence: 84%
“…In the case of C45, despite the dynamic nature of the protein, certain characteristics imply that it is a stable, water impenetrable structure [ 22 •• ]. Similar structural characteristics have been observed in other de novo [ 36 ] and natural proteins [ 57 ]. In many of these cases this may be due to the substrate conferring structural homogeneity on the active site, it remains to be experimentally determined whether this is the case for C45.…”
Section: How Important Is a Defined Structure In Catalysis?supporting
confidence: 84%
“…The established and conventional paradigm of protein evolution suggests that protein stability, or soluble and functional expression of proteins, is the dominant factor in determining evolvability (Bloom and Arnold, 2009; Tokuriki and Tawfik, 2009; Weinreich and Chao, 2005). Other studies indicate that protein structural folds cause differences in evolvability (Yip and Matsumura, 2013; Schulenburg et al, 2015; Dellus-Gur et al, 2013; Tóth-Petróczy and Tawfik, 2014). However, in our study, neither protein stability nor protein fold can account for variation in evolutionary potential between the MBL enzymes toward PMH activity.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, our understanding of the molecular mechanisms that underlie the relationship between genetic variation and evolvability is highly limited. It has been suggested that protein fold (Tóth-Petróczy and Tawfik, 2014; Yip and Matsumura, 2013; Schulenburg et al, 2015) and protein stability (Weinreich and Chao, 2005; Bloom and Arnold, 2009; Tokuriki and Tawfik, 2009) can shape evolvability, but these alone cannot explain the prevalence of epistasis and the enormous variation we observe in the evolvability of different genotypes. An in-depth understanding of the molecular constraints exerted by cryptic genetic variation is crucial to further develop our ability to decipher, predict and design the evolution of proteins.…”
Section: Introductionmentioning
confidence: 91%
“…Evolution of both the ordered and disordered states improved catalytic efficiency indirectly by bolstering the network of dynamic conformational fluctuations that productively couple with the reaction coordinate. 579…”
Section: Conclusion: Evolution Selected Protein Ensembles For Functionmentioning
confidence: 99%